2019
DOI: 10.3390/medsci7020029
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physicians’ Self-Compassion with Work Engagement, Exhaustion, and Professional Life Satisfaction

Abstract: Self-compassion has shown promise as an adaptive resource for coping with uncertainties and challenges. This study examined the relationship between self-compassion and professional wellbeing (work engagement, exhaustion, and professional life satisfaction) of physicians, who frequently face uncertainties and challenges in their clinical practice. Fifty-seven practicing physicians in Canada participated in the study. Overall, 65% of the participants were female; 47% were in the early-career stage; 49% were fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…This explains why job resources increase self-compassion. The mediating influence of self-compassion on the relationship between job resources and engagement confirms previous studies demonstrating that self-compassion increases engagement [35,36].…”
Section: Self-compassion As An Added Value To the Jd-r Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…This explains why job resources increase self-compassion. The mediating influence of self-compassion on the relationship between job resources and engagement confirms previous studies demonstrating that self-compassion increases engagement [35,36].…”
Section: Self-compassion As An Added Value To the Jd-r Modelsupporting
confidence: 87%
“…Research shows that self-compassion can enhance resilience [ 28 ], engagement, and mental well-being, and reduce distress [ 29 , 30 ] and burnout [ 31 , 32 ]. In addition, it has shown to be a predictor of increased mental wellbeing [ 33 , 34 ] and engagement [ 35 , 36 ]. Since self-compassion is an important resource for coping with negative emotions and cognitions resulting from stressors and adversity, it may buffer the relationship between job demands and distress.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the compassion intervention increased employees' self-compassion. This can be considered as crucial to both employees and organizations, as previous findings have shown associations between self-compassion and multiple work-related outcomes: for example, psychological strength and job performance (Reizer, 2019); job satisfaction (Abaci and Ardi, 2013); coping successfully with uncertain and challenging situations; increased professional well-being; and reduced work-related exhaustion (Babenko et al, 2019). Further related findings have included enhanced resilience (Delaney, 2018); increased self-improvement motivation (Breines and Chen, 2012); improved interpersonal and social relationships Canevello, 2012, 2017); and improved quality of team-based relational exchange and compassion toward others, through increases in trust and the feeling of social safety (Pinard et al, 2020), and through increased healthy self-care practices (Horan and Taylor, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among employees, previous studies have found that self-compassion has positive impacts on psychological strength, job performance (Reizer, 2019), and job satisfaction (Abaci and Ardi, 2013). Prior research has found that selfcompassion can act as a resource for coping with uncertain and challenging situations in ways that result in increased professional well-being and reduced work-related exhaustion (Babenko et al, 2019). Self-compassion increases motivation for self-improvement (Breines and Chen, 2012), and improves interpersonal and social relationships Canevello, 2012, 2017).…”
Section: Self-compassionmentioning
confidence: 99%
“…Reizer (2019) found that self‐compassion mediates the relationship between attachment styles and job performance, organizational citizenship behaviors, turnover intentions, and emotional exhaustion. Similarly, Babenko et al's (2019) findings indicate that self‐compassion is associated with increased job engagement and decreased emotional and cognitive exhaustion. Dev et al (2018) found that self‐compassion lowered the perceptions of barriers to compassion, potentially making it easier for care workers to deliver compassionate patient care.…”
Section: Systematic Literature Reviewmentioning
confidence: 86%